Public beliefs about lightning in Malaysia - A Rahim, Syakura; Gomes, Chandima; Trengove, Estelle; Ab Kadir, Mohd Zainal Abidin (IEEE, 2019)
Outcomes of a comprehensive survey on the public beliefs in Malaysia with regard to the nature of lightning and lightning safety have been presented. A questionnaire survey is done among 100 respondents, comprised of an equal number of participants from each gender. Despite the sample is biased towards educated layers of the society, the concepts of a sizable fraction of the sample are in contradiction with accepted scientific norms. Only 54% of the sample indicated disagreement with incorrect statements in the questionnaire. The percentage that agreed with correct statements is slightly below 50%. Such information plays a vital role in developing lightning safety guidelines for a given region. It is advisable to plan the safety modules in line with these beliefs, at least at the initial stage, rather than having myth-busting type approaches from the right beginning.